Efficacy analysis of ligamentum flavum preservation technique under unilateral biportal endoscopic in the treatment of lumbar disc herniation - Wei, Wen-Bo; Dang, Sha-Jie; Wei, Ling; Duan, Da-Peng (Frontiers in Surgery, 2025)
BackgroundUnilateral biportal endoscopic (UBE) surgery provides benefits like reduced invasiveness and swift recovery after surgery for individuals with lumbar disc herniation. A key factor in minimizing postoperative complications is the reduction of iatrogenic injury. This study retrospectively evaluates the effectiveness of the ligamentum flavum preservation technique during UBE for lumbar disc herniation and examines its technical application and clinical significance.MethodsFrom November 2023 to April 2024, 68 patients with lumbar disc herniation underwent unilateral biportal endoscopic (UBE) surgery via a single-side approach. Patients were allocated to either the conventional UBE group (Group T, n = 38) or the ligamentum flavum preservation group (Group P, n = 30) based on the surgical technique. Clinical outcomes were assessed using the Visual Analog Scale (VAS) for low back and leg pain, and the Oswestry Disability Index (ODI) at preoperative, postoperative 1, 3, 6 and 12 months. Operative time, length of hospitalization, postoperative drainage, the modified MacNab criteria, and complications were also recorded.ResultsPostoperative VAS and ODI scores demonstrated significant improvement in both groups; however, no statistically significant differences were observed between them at 1 day, 1 month, 3 months, 6 months, or 12 months following surgery. At 6 months postoperatively, the incidence of epidural fibrosis was significantly lower in the ligamentum flavum preservation group (Group P) compared to the conventional UBE group (Group T). In Group T, one case of cerebrospinal fluid leakage and two cases of nerve root injury were reported; all complications were transient and resolved within three months. Overall, the complication rates during follow-up showed no significant intergroup differences (P > 0.05).ConclusionsThe ligamentum flavum preservation technique applied during unilateral biportal endoscopic surgery enables effective removal of herniated disc material in cases of lumbar disc herniation, thereby relieving lower back pain and sciatica, enhancing lumbar function, reduce postoperative dural adhesions, and minimizing the risk of dural injury, cerebrospinal fluid leakage, epidural hematoma associated with ligamentum flavum resection.